Home Away from Home: Excitement or Agitation? Revisiting International Students Adaptability to Life in Malaysia - Jamaludin, Nor Lelawati; Farradina, Syarifah; Wee, Nur Melissa binti Mohammad Faisal; Sadik, Mohd Zaki Bin; Jamil, Norina Ahmad; Mahpar, Nurul Salizawatee; Sani, Nur Zania Azurin Abdullah (Advances in Social Sciences Research Journal, 2024)
The act of relocating from one’s nation of origin is frequently perceived as a formidable experience in the lives of sojourners. Several studies and models examining adjustment speculate that either euphoria or agitation can characterize the initial period of a vacation. This study examines the initial experiences of 9 International Postgraduate students through a case study approach, utilising interviews to determine whether their early phase of adjustment was characterised by feelings of euphoric or agitated in nature. The results of the study indicated that participants reported an array of experiences, some of which were positive and others negative. Individual preferences and previous encounters influenced these experiences. Another significant discovery of this research pertained to the pre-departure phase of the students’ sojourn, indicating that the psychological aspects of the experience commence well in advance of their initial arrival in Malaysia. This study has the potential to provide a foundation for future research and inform the Department of International Affairs in developing programme components that facilitate the adaption of international students.